Mesenteric Paraganglioma-A Cyst in The Mist - B, Saniha P; Jadhav, M N; Kittur, S K (Annals of Pathology and Laboratory Medicine, 2020)
Extraadrenal paraganglioma is rarely found in the mesentery. It accounts only for 5-10% of cases and may present incidentally as abdominal mass. We report a case of 30 year old male presented as mass per abdomen. A differential diagnosis of neurogenic tumor or cystic mesothelioma was considered based on CT-abdomen. Histopathological examination showed features of mesenteric paraganglioma and confirmed on immunohistochemistry. This case report highlighted several important key issues regarding diagnosis of paraganglioma, including malignant or metastatic potential, recurrence rate, pre and postoperative imaging study and lifelong follow-up of the patient.